Preparing sandwiches, appetizers and salads [videorecording] - Inducil, Mark (Meridian Education Corp., 2010)
Having the skills and knowledge required to prepare and present appetizers, sandwiches and salads is crucial to successful operation of any commercial kitchen or catering business. This program takes you through the steps involved in making, preparing, and presenting these ever evolving dishes while discussing useful tips that will enhance the quality of your food preparation.